Analisis Pengaruh Leverage, Likuiditas, Struktur Modal, Earning Per Share dan Profitabilitas Terhadap Nilai Perusahaan - Berlianna Devita Siwa; Lintang Kurniawati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyze the influence of leverage, liquidity, capital structure, earnings per share (EPS), and profitability on company value in the food and beverages subsector companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2022. Using a quantitative approach and secondary data, the analysis was conducted using multiple regression to examine the relationship between these variables and company value measured by the Price to Book Value (PBV) ratio. The results show that leverage, liquidity, capital structure, and EPS do not have a significant impact on company value, while profitability positively influences company value. The limitations of this study include a limited sample and the fact that the variables used explain only 17% of the variation in company value. Future research is suggested to extend the research period, use a more diverse sample, and add other independent variables such as LDER, GPM, and NPM..